2020
DOI: 10.3389/fpsyt.2020.00695
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Attitudes, Anxiety Status, and Protective Behaviors of the University Students During the COVID-19 Outbreak in Turkey

Abstract: A new coronavirus disease began on 31 December 2019 in Wuhan/China and has caused a global outbreak in only a few months resulting in millions being infected. In conjunction with its’ physical side effects, this outbreak also has a tremendous impact on psychology health. This study aims to assess the spread and frequency of protective behaviors, emotional and anxiety status among the Turkish population using a rapid survey during the COVID-19 outbreak. An online questionnaire was administered to 3,040 responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
2
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 33 publications
2
84
2
14
Order By: Relevance
“…30 This could be due to variation in the outbreak magnitude, educational status, information accessibility, and the study period. 18,28 In this study only 38.0% of urban residents had high preventive behavior towards the COVID-19 outbreak. This figure is lower than the finding from Iran that reported high preventive behaviors related to the COVID pandemic.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…30 This could be due to variation in the outbreak magnitude, educational status, information accessibility, and the study period. 18,28 In this study only 38.0% of urban residents had high preventive behavior towards the COVID-19 outbreak. This figure is lower than the finding from Iran that reported high preventive behaviors related to the COVID pandemic.…”
Section: Discussionmentioning
confidence: 51%
“…[25][26][27] These discrepancies could be attributed to differences in assessment tools, study period (data was being anxiousness toward pandemic increase at beginning, then decrease and finally collected after a few months when the community gives less attention. Community reaction and stable, 28 variations in sociodemographic characteristics, environmental and sociocultural determinants that could contribute to handle the psychiatric issues during the pandemic. 29 The study also indicated that a majority of the urban residents had a moderate degree of risk perception towards the COVID pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The study has found that 44% of students reported a moderate level of worrisome and fear of catching COVID-19, while 80% of students reported a 'severe level' of scare and worries about their close relatives' health. The authors expected that the high levels of anxiety among the students in their study could be attributed to shifting to online learning along with other pandemic control measures such as social isolation and financial constraints (Akdeniz et al, 2020). Similarly, the aforementioned worries were also reported by the students in our study as part of their major concerns during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 53%
“…First, the COVID-19 pandemic has become a major life stressor that has direct and indirect influences on students’ psychological well-being. The direct influences include the students’ emotional feelings toward COVID-19 (eg, fear of being infected) [ 19 - 21 ], and the indirect influences include the government’s reaction in relation to transmission control (eg, feeling depressed when receiving threatening COVID-19 news or feeling lonely because of social distancing) [ 7 ]. Second, university students are at a critical life-transition period (ie, school-to-work transition [ 22 ]).…”
Section: Introductionmentioning
confidence: 99%